Are functional outcomes and reoperation rates really better than those of cementless stems in displaced femoral neck fractures? An updated systematic review and meta-analysis of randomized controlled trials in current-generation stem designs. Issue 10 (19th August 2021) - Fu, Chun-Wei; Ma, Hsuan-Hsiao; Liu, Yueh-Ching; Lu, Yung-Chang; Huang, Tung-Fu; Chang, Ming-Chau; Chen, Wei-Ming
Abstract : Background: The aim of the study was to conduct a systematic review and meta-analysis to compare the functional outcomes and reoperation rates of cemented and cementless hip arthroplasty for treating displaced femoral neck fractures in elderly patients. Methods: Systematic searches were conducted of literature up to December 2018 on PubMed, Embase, Cochrane, and Web of Science for randomized controlled trials (RCTs) concerning current-generation stem designs only. Two reviewers independently determined eligibility, extracted the outcome data and assessed the risk of bias of eligible studies. The follow-up data and complication rates were pooled by using random-effects models and fixed-effects models, with mean differences and risk ratios for continuous and dichotomous variables, respectively. Results: Eight RCTs involving 1361 patients (1361 hips) were included in the meta-analysis. Cemented stems were associated with fewer implant-related complications (odds ratio [OR] = 0.303; 95% confidence interval [CI], 0.185%-0.496%; p < 0.001) and reoperations (OR = 0.492; 95% CI, 0.247%-0.977%; p = 0.043). There were no statistically significant differences between groups in functional outcomes, including those assessed by the EuroQol(EQ)-5D and Harris Hip Score, mortality rates, major systemic complications, minor local complications, operation times, intraoperative blood losses, and lengths of hospital stays. Conclusion: In treating displaced femoral neck fracture in elderly patients with hip arthroplasty with current-generation stems, cemented stems were found to have fewer implant-related complications and reoperations than those of cementless stems. Functional outcomes and mortality rates were similar between the groups.